An Empirical Study of Factors Influencing E-Commerce Adoption/Non-Adoption in Slovakian SMEs. Issue 3 (2nd July 2016) - Walker, John H.; Saffu, Kojo; Mazurek, Marica
ABSTRACT: While the global emergence of e-commerce has led businesses to take advantage of the technologies available to them to enhance their use of e-commerce, small and medium-sized enterprises (SMEs) are known for not adopting information technology to create jobs. Due to the dearth of studies of SME adoption of technology in transitioning European countries such as Slovakia, (Saffu, Walker, and Mazurek2012 ), it is imperative to understand the factors that differentiate SME e-commerce adopters from non-adopters. Adoption and non-adoption factors of 230 Slovakian SMEs were empirically examined using logistic regression. Compatibility and Organizational Readiness, Decision and Operational Aids, and External Pressure were significant for discerning e-commerce adoption. Practical, policy, and research implications are presented. This study goes beyond the determinants of e-commerce adoption and contributes to the understanding of factors that distinguish between adopters and non-adopters of e-commerce for Slovakian SMEs.